Vitamin, protein and essential mineral enhancement of cereal crops for food security - Zhu C.; Naqvi S.; Gómez-Galera S.; Pelacho A.; Capell T.; Christou P. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
In the developing world 840 million people are chronically undernourished. It is estimated that more than half of the world's population suffers from diseases caused by dietary deficiencies and inadequate supplies of essential micronutrients. The endosperm tissues of cereal crops (maize, wheat, and rice) serve as major staple foods worldwide. However, they are deficient in essential vitamins (A, E, C and folate), lysine, and minerals (iron, selenium and zinc). The cloning of a near complete set of identified genes required for the biosynthesis of vitamins, lysine and methionine, and for the absorption and bioavailability of Fe, Se and Zn during the past decade, combined with the capabilities to introduce multiple transgenes into cereal crops in recent years, makes it possible to simultaneously enhance all such micronutrients in agriculturally important cereal crops. Our ongoing research towards the simultaneous enhancement of vitamins (A, E, C and folate), essential amino acids (Lys and Met), and minerals such as Fe, Se and Zn, in cereal endosperm tissues by genetic manipulation in order to combat deficiencies in human populations will be presented.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)